Komplexität und Normenklarheit - oder: Gesetze sind für Juristen gemacht - Emanuel Vahid Towfigh (Max Planck Institute for Research on Collective Goods, 2008)
The paper deals with the complexity of legal norms and the instrument the German constitutional law establishes to control it, namely the requirement of normative clarity. First, I introduce a definition of complexity of written legal norms, conceptualized by their density (number of items to be considered) and interdependencies (within a norm and of different norms), thus focussing on the complexity of the underlying rule, rather than its language. Complexity is then described as a primarily cognitive problem, with reflexes on the time and monetary scales. The view taken here is therefore a subjective one, setting out from the individual who tries to understand a legal text. The technicality of a norm can reduce complexity for those trained in the law, and at the same time raise it for laypeople. Legal doctrine, too, aims at reinforcing consistence and reducing complexity. The requirement of normative clarity, however, is not a means to reduce complexity, but only to control it. Normative clarity is held to be founded in the principle of the separation of powers, and its measure is the executability of the law. Against concurrent views, I therefore argue that it is not the norm's addressee who must understand the norm, but rather lawyers. Only then can the problem of legal complexity be handled in systems that rely heavily on statutory law. The argument is supported by theoretical, behavioural and doctrinal reasons.
Keywords: 340; Recht; Rechtspolitik; Deutschland